Application of a ImageJ-Based Method to Measure Blood Flow in Adult Zebrafish and Its Applications for Toxicological and Pharmacological Assessments - Ferry Saputra; Tzu-Ming Tseng; Franelyne P. Casuga; Yu-Heng Lai; Chih-Hsin Hung; Chung-Der Hsiao (Biology)
Blood flow is an important physiological endpoint to measure cardiovascular performance in animals. Because of their innate transparent bodies, zebrafish is an excellent animal model for assessing in vivo cardiovascular performance. Previously, various helpful methods for measuring blood flow in zebrafish larvae were discovered and developed. However, an optimized method to measure blood flow in adult zebrafish has not been reported. In this paper, the tail fin region was selected as target for blood flow measurements using the Trackmate method, provided by ImageJ platform. Based on power statistic calculations, the aortic vessel at the tail base was selected, and other parameters, such as ambient temperature, were investigated for method standardization, in order to minimize experimental variation. The method was also validated using fenpropathrin and ponatinib, which showed some cardiac alterations in a previous zebrafish study. We also checked the versatility of this method by following the same setup in black tetra and medaka and found that this method performed well. However, our results show that heavy pigmentation, like that found in tiger barb, and overlapping vessels, like those in parrot fish, make it hard for this method to perform well. Overall, an optimized protocol was used for the first time to measure blood flow velocity in adult wild-type zebrafish without the aid of transgenic lines or fluorescent dye.